1988
DOI: 10.1016/s0006-3495(88)83136-9
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of the actomyosin bond in the filament array of muscle fibers

Abstract: The interaction between actin and myosin in the filament array of glycerinated muscle fibers has been monitored using paramagnetic probes and mechanical measurements. Both fiber stiffness and the spectra of probes bound to a reactive sulfydral on the myosin head were measured as the actomyosin bond was weakened by addition of magnesium pyrophosphate (MgPPi) and glycerol. In the absence of MgPPi, all myosin heads are attached to actin with oriented probes. When fibers were incubated in buffers containing MgPPi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 47 publications
9
66
1
Order By: Relevance
“…The instantaneous stiffness of these MSL-labeled fibers during contraction is 75-85% of the rigor stiffness, as previously reported for unlabeled fibers (21). If the small fraction of heads with rigor-like orientation is responsible for this high stiffness, they must have much higher stiffness than in rigor (10). However, ifwe assume that the fraction of rigor stiffness (75-85%) is the fraction of attached heads, then at most 17% (13%/75%) of the attached heads exhibit rigor-like orientation, since all the heads are bound in rigor (22,23).…”
Section: Methodsmentioning
confidence: 99%
“…The instantaneous stiffness of these MSL-labeled fibers during contraction is 75-85% of the rigor stiffness, as previously reported for unlabeled fibers (21). If the small fraction of heads with rigor-like orientation is responsible for this high stiffness, they must have much higher stiffness than in rigor (10). However, ifwe assume that the fraction of rigor stiffness (75-85%) is the fraction of attached heads, then at most 17% (13%/75%) of the attached heads exhibit rigor-like orientation, since all the heads are bound in rigor (22,23).…”
Section: Methodsmentioning
confidence: 99%
“…These assumptions have all been questioned (25)(26)(27), but their validity is not required for the main conclusions in the Discussion. Determination of Myosin Head Concentration.…”
Section: [2]mentioning
confidence: 99%
“…First, the number of attached crossbridges may have been overestimated by comparing stiffness relative to rigor (e.g., as mentioned earlier, in the rigor fiber, all of the myosin heads may not be contributing to stiffness) (25,26), and this would have led to an underestimation of the calculated value of g (see Eq. 1 in Methods).…”
mentioning
confidence: 99%
“…A third possibility is that axial stiffness is a measure of the fraction of myosin molecules interacting with actin, regardless of whether the interaction involves one or both heads of the myosin molecule, while the radial stiffness is a measure of the fraction of myosin heads attached. Fajer et al (1988) and Pate & Cooke (1988), based on EPR studies, suggested that in the axial direction, a single-headed nucleotide-free attached cross-bridge was as stiff as a double-headed nucleotide-free one. Finally and quite likely, the overall elastic properties.…”
Section: Radial Elasticity Of Cross-bridges In Musclementioning
confidence: 99%